by Cyndy

(United States)

Let's list down the information:

Number of Ride (n) | Cost |

1 | 2.00 |

2 | 2.50 |

Let the cost of the rides be

Hence, when n = 1, we have:

C = 2.00 ----- (1)

When n = 2, the cost increase by 0.50. Hence:

C = 2.00 + 0.50 ----- (2)

To write an expression that caters for (1) and (2), note that in (2), we can multiply the term,

C= 2.00 + 0.50(n-1)----- (3)

Why? This is because the

C = 2.00 + 0.50(1-1)

= 2.00 + 0.50(0)

= 2.00

And, when n = 2, the

C = 2.00 + 0.50(2-1)

= 2.00 + 0.50(1)

= 2.00 + 0.50

= 2.50

Hence, the expression that we are looking for is:

C = 2.00 + 0.50(n-1)For n =1 and n =2